District and City Clasterization Based on Adipura Assessment in The Region of Indonesia Using the Fuzzy Methodc-Means - Syariful Alim; M Mahaputra Hidayat; R Dimas Adityo; Elta Deka Wilinda (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Adipura is an award for Indonesian cities that succeed in cleanliness and management of the urban environment. Adipuraisorganizedby the State Ministry ofEnvironment.Adipurais actually usedasatool to encourage the motivation of government officials and the community to improve and improve environmental hygiene conditions in Indonesia. The problem istodeterminetherecipient ofAdipuratakes2weeksto selectRegenciesandCities in all regions of Indonesia, in this study there were 374 Cities and Regencies collected. Clustering is a method of grouping based on the size of closeness (similarity). Clustering is different from a group, if a group means the group is in the same condition, if not, then definitely not the group. One method that can be usedin clusteringis fuzzy c-means. In the concept ofFuzzyC-Means firstdetermine the center of the cluster, which will mark the average location of each cluster which is then carried out the process of repairing the cluster center and the degree ofmembership of the point to theminimization of objective functions that describe the distance from the data points given to the center of the weighted cluster by the degree of membership of that point. From the results of testing a regional clustering systemthat deservesAdipura with the result that each cluster in each processgets avalue that is always changing, so it cannot determine the labeling of a patent. Data greatly influences the time for application processing. The more data it will take more time for the fastest time is in the Big City category while the longest application execution time is in small cities with a total data of 273.